A CURRICULUM STUDY: HUKOU QINGYANG OPERA KNOWLEDGE TRANSMISSION IN JIANGXI PROVINCE, CHINA - Mei, Jiaqi; Thotham, Awirut (International Online Journal of Education and Teaching, 2023)
Qingyang opera is a cultural feature of Hukou, with the "Xiulan Ban" singing on the banks of Poyang Lake and the Yangtze River. The objective was to study the transmission process of Hukou Qinyang Opera knowledge in Jiangxi Province, China. The research tools include interviews and observation to obtain research data. Qualitative research uses observation, experimentation, and analysis to determine the essential characteristics of things. The informants are classified into three groups: key, Qingyang opera performers, and general. The results showed that the transmission of Qinyang Opera has two systems: one is the informal transmission, with local artists as the main transmission, and the second is the formal transmission, with university and academic institution participants as the main participants in the transmission.